Performing inequality: Feminist performative acts as protest gestures. (1st October 2016) - Marchevska, Elena
This article will look at three case studies of performative political protest, where female activists are raising awareness of the precarious conditions of their lived experience in economic neo-liberalism. The research is focused on links between Focus E15 Mothers Group in London, the #protestiram movement in Macedonia and #direnkahkaha (resist laughter) in Turkey. I will analyse these protest movements' performative acts and argue that these acts are strategically used to draw attention to the inequality faced by women.